Synthesize of gold nanoparticles with 532 NM and 1064 NM pulse laser ablation - Norsyuhad, W. (Penerbit UTM Press, 2016)
The effect of laser wavelength on gold nanoparticle fabrication is reported. Colloidal solutions of gold nanoparticles were prepared by pulsed laser ablation technique in deionized water. A Q-switched Nd:YAG laser with constant energy of 65mJ and operation at fundamental wavelength and second harmonic generation was utilized as a source of energy. Fabricated particles were characterized by using Smart Nanoparticles Measurements (SNM) system. The average diameters of gold nanoparticles achieved as19 nm and 12 nm corresponding to 1064 nm and 532 nm respectively. The fragmentation of colloidal particles by self-absorption of laser pulses is the responsible mechanism to cause for reduction.